Study on the efficacy of Centella Asiatica on Student’s Memory and Attention Improvement - Putra, Yovan Pino; Wibawa, Basuki; Rusmono; Kamil, Mausul; Prasetyohati, Emy (International Journal of Psychosocial Rehabilitation, 2020)
Centella asiatica (CA), locally known as pegagan, is a common herb plant used in many Indonesian dishes. CA is also an Ayurvedic herb used to enhance memory and nerve function (Shiva, 2005). To investigate the potential use of CA in improving memory and attention, we examined the effects of daily consumption of CA for 60 days in 57 students divided into 3 groups (2 study and 1 control groups) in a single blind study. Measurements used are memory sub test of IST and Deary-Liewald reaction time test. Paired t-test was applied to know the result within the group and unpaired t-test was used to know the result in between the group. This research is useful to shed lights on the therapeutic benefits of this daily-consumption plant.